New species and records of Cerambycinae and Lamiinae (Coleoptera: Cerambycidae) from the Neotropical Region - Martins, Ubirajara R.; Galileo, Maria Helena M. (Zootaxa, 2013)
New species are described in Cerambycinae, in Elaphidiini: Eurysthea parva sp. nov. from Ecuador (Loja); in Hexoploni-ni: Hexoplon rubriceps sp. nov. from Ecuador (Napo); in Neoibidionini: Cycnidolon praecipuum sp. nov. from Bolivia (Santa Cruz); in Pteroplatini: Pteroplatus caudatus sp. nov. from Colombia (Cundinamarca); Pteroplatus pallidicolor sp. nov. from Peru (Cajamarca); in Tillomorphini: Epropetes tristis sp. nov. from Panama (Darien) and Euderces elachys sp. nov. from Ecuador (Manabi). In Lamiinae, Agapanthiini: Trichohippopsis barbatulus sp. nov. from Ecuador (Manabi) is described. Chromatic variation in Gnomidolon pulchrum Martins, 1960 (Hexoplonini) is discussed. New records are given for: Eburodacrystola pickeli Melzer, 1928 and Eburodacrys cunusaia Martins, 1997 (Eburiini) for Bolivia; Tetranodus tropipennis Chemsak, 1977 (Tillomorphini) for Nicaragua and Ecuador; and Pteroplatus transversalis Breme, 1844 (Pteroplatini) for Ecuador.